(3TQM eLehY GdHMQjf hedJbi GdfjQjfs - (3CMeO Hf Ydj Hf KYdH Hf GdSGYGJj GdHZOGOj , eXaQ GdOjf,J (B694 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH Gdhba s
(3BNQgG (B:s
(3jfJgi HfgGjI aUd GdeYGbd (B( (3ef cJGH GdOjGJ (B) s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJH GdeJf HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdabg GdMfajs